PENGARUH BOOKLET CEGATINGTERHADAP PENGETAHUAN IBU TENTANG PENCEGAHAN STUNTING PADA ANAK USIA 1-5 TAHUN DI PUSKESMAS 7 ULU PALEMBANG - Sri Tirtayanti (IKesT Muhammadiyah Palembang, 2024)
The Effect of Educational Video on Mother's Knowledge about Stunting in children aged 1-5 years at the Palembang 7 ulu health center. ABSTRACT Background: Stunting is a condition of failure to thrive in children under five due to chronic malnutrition so that children are shorter for their age. Malnutrition can occur from infancy in the womb and in the early days after birth, but only appears after the child is 2 years old. The incidence of stunting Currently, approximately 9 million out of a third of the total number of children under five (37.2%) in Indonesia suffer from stunting. Research objective: To determine the effect of educational videos on mothers' knowledge about stunting prevention in children aged 1-5 years at the 7 Ulu Palembang Health Center. Research method: This study used a pre-post pre-experimental approach with a pretest-posttest design. The characteristic of this research is to reveal the results of treatment in one group, by involving a group of mothers in the health center who are given Health Education for stunting prevention on mother's knowledge, the sampling technique uses purposive sampling. Results: The value of mother's knowledge before being given stunting prevention educational videos to children aged 1-5 years at Puskesmas 7 Ulu Palembang with a median of 12, while the value of mothers' knowledge after being given stunting prevention educational videos to children aged 1-5 years at Puskesmas 7 Ulu Palembang with a median of 15. The bivariate test in this study used the non-parametric Wilcoxon test with a p value of 0.001 <0.05 so that Ha was accepted. Conclusion: There is an effect of educational videos on mothers' knowledge about stunting prevention in children aged 1-5 years at Puskesmas 7 Ulu Palembang. Keywords: Stunting, Video Education, Mother's knowledge.